UJI ORGANOLEPTIK BAKSO BERBAHAN BAKU DAGING SAPI YANG DISUBSTITUSI DAGING DOMBA - Aaf Falahudin; Rachmat Somanjaya; Tatan Rustandi (UNIVERSITAS MAJALENGKA, 2020)
This study aims to analyze the effect and the best dose of beef meatballs substituted with lamb meat on the organoleptic properties of meatballs. The experimental design used was a Completely Randomized Design with 5 treatments and 4 replications. The treatments applied are as follows: B0 = 100% beef + 0% lamb meat, B1 = 75% beef + 25% lamb meat, B2 = 50% beef + 50% lamb meat, B3 = 25% beef + 75% lamb meat, B4 = 0% beef + 100% lamb meat. The results showed that hedonic panelists still liked the color and texture of all beef meatballs substituted with lamb meat on a hedonic scale rather like to like. However, for the smell and taste of meatballs, lamb substitutes are used for a maximum of 50% without affecting the level of preference.